2017
DOI: 10.1007/s00192-016-3256-5
|View full text |Cite
|
Sign up to set email alerts
|

Reoperations for mesh-related complications after pelvic organ prolapse repair: 8-year experience at a tertiary referral center

Abstract: In a referral center the global rate of reinterventions for mesh-related complications after POP repair is 2.8%. The surgical treatment of mesh complications appears to be a safe and effective procedure with cure of the symptoms in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
6
33
3
2
Order By: Relevance
“…Most studies reporting mesh complications have focused on the time interval between insertion of mesh and excision of the exposed mesh instead of detection of mesh exposure. 20,21 The exact location and size of the mesh exposure are sometimes inadequately reported. 14,20 Many studies have investigated mesh-related complications from mesh reconstructive surgery for pelvic organ prolapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reporting mesh complications have focused on the time interval between insertion of mesh and excision of the exposed mesh instead of detection of mesh exposure. 20,21 The exact location and size of the mesh exposure are sometimes inadequately reported. 14,20 Many studies have investigated mesh-related complications from mesh reconstructive surgery for pelvic organ prolapse.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The exact location and size of the mesh exposure are sometimes inadequately reported. 14,20 Many studies have investigated mesh-related complications from mesh reconstructive surgery for pelvic organ prolapse. However, there is limited information on such complications in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…A few published studies based on small sample sizes have reported cases of removal of prosthetic material to treat chronic postoperative pain related to either suburethral tape or inguinal hernia repair. [17][18][19][20][21][22][23][24] The present series constitutes the largest published series of removal of prosthetic material for chronic pain with acceptable results, as almost two-thirds of patients were improved.…”
Section: Discussionmentioning
confidence: 99%
“…31 Surgical treatment of mesh-related complications accounted for 7% of TVM procedures in our center. 32 Risk factors reported to be associated with complications included: operative technique, surgeon experience, previous prolapse repair, concomitant hysterectomy, inverted T colpotomy during concomitant hysterectomy, total vaginal mesh repair, mesh properties, younger age at the time of surgery, sexual activity, and smoking. 33 Our study was not able to identify vaginal microbiotic dysbiosis as a factor associated with mesh exposure.…”
Section: Commentsmentioning
confidence: 99%